The adoption of ecologically conscious consumer behaviors: exploring the association of materialism and voluntary simplicity lifestyles - Cardigo, Ana Cristina de Jesus (2008)
In most of the developed economies it is common to find high levels of consumption, most of the times connected to the pursuit of status. The pattern of consumption dictated by contemporaneous society through persuasive marketing messages promises a more exciting life, through acquisition. However, to keep a high level of consumption it is necessary to have financial resources. This means that more time dedicated to work is needed and/or get financial loans. Getting trapped in this vicious cycle – work/earn/spend – without personal time generates stress and anxiety. Therefore, many individuals are becoming aware that materialism does not imply happiness. This awakening may also be connected to the finding that higher level of consumption has a higher impact in surrounding environment than the individual perceived until then, in social, ecological and even animal terms. A new way of consumption, more aware, is rising, and it is called ethical consumption. Due to its multiple motivations and expressions it is complex to analyze. This work will specifically focus on voluntary simplifiers. These consumers, besides the concerning with acquired products, have chosen to reduce, voluntarily, their level of consumption. As consumption has impact on surrounding environment, it is suspected that materialist individuals have fewer concerns over the environment than voluntary simplifiers, considered more aware. Therefore, this study intends to analyze the connection between ecological conscious consumer behaviors and environmental concern, and the impact of values such as altruism, non-generosity and perceived consumer effectiveness, for both groups of materialistic individuals and voluntary simplifiers.